Cracking the Codes: Students' Preferred Strategies to Enhance Exam-Based Academic Achievement in Higher Education - Sharma, Lok Raj (International Research Journal of MMC, 2025)
Identifying students’ preferred learning strategies plays a substantial role in enhancing academic achievement in higher education. This article investigates students’ preferred strategies for enhancing exam-based academic achievement in higher education. A cross-sectional survey design was employed, utilizing a structured questionnaire consisting of 10 multiple-choice items measured on a nominal scale. The total population comprised 516 BBA and BBM first, third, fifth, and seventh semester students studying at Makawanpur Multiple Campus, Hetauda, Nepal. A sample of 221 students was determined using a sample size calculator with a 95% confidence level and a 5% margin of error. Proportionate stratified sampling was employed to ensure adequate representation across academic strata. A pilot study was conducted among 22 (10 % of the sample size) students. Fleiss’s multi-rater Kappa showed an acceptable reliability of instrument, 0.614 in the pilot study and 0.663 in the main study. Primary data were collected through the questionnaire in 2025 after obtaining written consent from the students to ensure confidentiality, whereas secondary data were reviewed from scholarly journals, academic books, and credible websites published between 2021 and 2025. Descriptive statistics (frequencies and percentages) and Monte Carlo simulation of the Chi-square test were used to analyze the primary data and examine any association between students’ strata and their preferred strategies. The findings indicate that students favored a range of strategies, including collaborative learning, structured daily study routines, key point reviews, interactive classes, the use of online platforms, continuous assessments, and personalized feedback. Moreover, students valued innovative teaching methods, access to well-equipped libraries and study materials, regular revision sessions, academic discussions, and student support services such as advising and counseling. Monte Carlo chi-square p-value (p > .05) showed no statistically significant association between students’ strata and their preferred study strategies at the 0.05 level. These findings can guide teachers and educators in refining instructional methods and inform policies that enhance student learning outcomes in higher education.